Chitosan Increases Tomato Root Colonization by Pochonia chlamydosporia and Their Combination Reduces Root-Knot Nematode Damage - Escudero, Nuria; Lopez-Moya, Federico; Ghahremani, Zahra; Zavala-Gonzalez, Ernesto A.; Alaguero-Cordovilla, Aurora; Ros-Ibañez, Caridad; Lacasa, Alfredo; Sorribas, Francisco J.; Lopez-Llorca, Luis V. (Frontiers in Plant Science, 2017)
The use of biological control agents could be a non-chemical alternative for management of Meloidogyne spp. [root-knot nematodes (RKN)], the most damaging plant-parasitic nematodes for horticultural crops worldwide. Pochonia chlamydosporia is a fungal parasite of RKN eggs that can colonize endophytically roots of several cultivated plant species, but in field applications the fungus shows a low persistence and efficiency in RKN management. The combined use of P. chlamydosporia with an enhancer could help its ability to develop in soil and colonize roots, thereby increasing its efficiency against nematodes. Previous work has shown that chitosan enhances P. chlamydosporia sporulation and production of extracellular enzymes, as well as nematode egg parasitism in laboratory bioassays. This work shows that chitosan at low concentrations (up to 0.1 mg ml-1) do not affect the viability and germination of P. chlamydosporia chlamydospores and improves mycelial growth respect to treatments without chitosan. Tomato plants irrigated with chitosan (same dose limit) increased root weight and length after 30 days. Chitosan irrigation increased dry shoot and fresh root weight of tomato plants inoculated with Meloidogyne javanica, root length when they were inoculated with P. chlamydosporia, and dry shoot weight of plants inoculated with both P. chlamydosporia and M. javanica. Chitosan irrigation significantly enhanced root colonization by P. chlamydosporia, but neither nematode infection per plant nor fungal egg parasitism was affected. Tomato plants cultivated in a mid-suppressive (29.3 ± 4.7% RKN egg infection) non-sterilized clay loam soil and irrigated with chitosan had enhanced shoot growth, reduced RKN multiplication, and disease severity. Chitosan irrigation in a highly suppressive (73.7 ± 2.6% RKN egg infection) sterilized-sandy loam soil reduced RKN multiplication in tomato. However, chitosan did not affect disease severity or plant growth irrespective of soil sterilization. Chitosan, at an adequate dose, can be a potential tool for sustainable management of RKN.